Communists in Harlem During the Depression - Nelson, Bruce (Labour / Le Travail, 1985)
This article reviews the book, "Communists in Harlem During the Depression," by Mark Naison.
Keywords: COMMUNISTS in Harlem During the Depression (Book); Communism; NAISON, Mark, 1946-; Nonfiction; REVIEWS; books